Persepsi pelajar terhadap penggunaan kaedah Bimbingan Rakan Sebaya (BRS) untuk pembelajaran kosa kata Arab / Nabihah Yusof ... [et al.] - Yusof, Nabihah; Baharudin, Harun; Lubis, Maimun Aqsha; Yusoff, Muhammad Saiful Anuar (2018)
inferred that some difficulties in vocabulary mastery namely lack of interaction and learners’ decreasing performance in communication are caused by the stimulation of learners’ surrounding during classroom learning. This article explores learners’ perception of implementation of Peer Tutoring (PT) in Arabic vocabulary mastery. 50 secondary school students of form four were involved in this study in which quantitative instrumentation of survey form is applied. Likert scale of 1-5 in measuring the degree of perception is used. Accordingly, descriptive statistics of mean and standard deviation were computed in order to report the findings. It is found that the learners’ perception of the use of Peer Tutoring (PT) method to learn Arabic vocabulary is positive with the average mean score of 4.10. In summary, the Peer Tutoring (PT) method is suitable to be implemented as an effective learning technique which provides a convenient platform for the learners to interact using the target language. As a result this technique can also enhance and strengthen vocabulary mastery among learners.